PENERAPAN MEDIA GAMBAR SERI UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI SEDERHANA SISWA KELAS II SEKOLAH DASAR - Rahayu, Putri Anggun (2017)
This research was a classroom action research (CAR) with the adapted model from Kemmis and Mc. Taggart using two cycles on the implementation of series picture media to improve the simple narrative writing skill of second grader students in primary school. This research was conducted in one primary school at Sukajadi, Bandung. The subjects of this research were 29 students from class of IIC. This research aimed (1) to know the process of learning by applying series picture media to improve the skills of writing simple narrative essay on the second grade students of primary school; (2) to know the improvement of students' narrative writing skill after the implementation of the series picture media. This research was motivated by the lack of interest of students towards writing. Preliminary data indicated that 79.32% of students whose value were still below KKM (Criteria Completed Minimum) so they had not yet completed the learning. The results of this research showed that there was improvement of students' writing skill by applying the series picture media. The average value of the class in the first cycle was 63.27% with 37.98% learning completion, while in the second cycle had increased to 72.75% with 72,41% learning completion. According to the results of this research, teachers were advised to apply the serial images media to improve writing skill of students.---- Penelitian ini adalah penelitian tindakan kelas (PTK) yang mengadaptasi dari model Kemmis dan Mc. Taggart dengan dua siklus mengenai penerapan media gambar seri untuk meningkatkan keterampilan menulis karangan narasi sederhana siswa kelas II sekolah dasar yang dilaksanakan di salah satu SD di kecamatan Sukajadi, kota Bandung. Subjek penelitian ini adalah 29 peserta didik kelas IIC. Penelitian ini bertujuan untuk (1) mengetahui proses pembelajaran dengan menerapkan media gambar seri untuk meningkatkan keterampilan menulis karangan narasi sederhana siswa kelas II sekolah dasar; (2) mengetahui peningkatan keterampilan menulis karangan narasi sederhana siswa di kelas II sekolah dasar setelah menerapkan media gambar seri. Penelitian ini dilatarbelakangi oleh kurangnya ketertarikan siswa terhadap menulis. Data awal menyebutkan bahwa 79,32% siswa nilainya masih di bawah KKM (Kriteria Ketuntasan Minimal) sehingga belum tuntas belajar. Hasil penelitian yang dilakukan menunjukkan adanya peningkatan keterampilan menulis siswa dengan menerapkan media gambar seri. Nilai rata-rata kelas pada siklus pertama sebesar 63,27 dengan ketuntasan belajar 37,98%, sedangkan pada siklus dua mengalami peningkatan sebesar 72,75 dengan ketuntasan 72,41%. Menyimak hasil penelitian tersebut, untuk para guru disarankan menerapkan media gambar seri untuk meningkatkan keterampilan menulis karangan siswa.